Optimising management of deferasirox therapy for patients with transfusion‐dependent thalassaemia and lower‐risk myelodysplastic syndromes. (27th July 2018) - Kattamis, Antonis; Aydinok, Yesim; Taher, Ali
Abstract: Effective iron chelation therapy is an important part of treatment in patients with transfusion‐dependent thalassaemia and lower‐risk myelodysplastic syndromes (MDS). Key strategies for optimising iron chelation therapy include ensuring good adherence and preventing and managing adverse events (AEs). Good adherence to iron chelation therapy with deferoxamine and deferasirox has been linked to improved survival and/or reductions in complications related to iron overload; however, maintaining good adherence to iron chelators can be challenging. Patients with transfusion‐dependent thalassaemia or lower‐risk MDS showed better adherence to the deferasirox film‐coated tablet (FCT) formulation than to the deferasirox dispersible tablet formulation in the ECLIPSE trial, reflecting in part the improved palatability and convenience of deferasirox FCT. As well as affecting adherence, AEs may lead to dose reduction, interruption or discontinuation, resulting in suboptimal iron chelation therapy. Preventing and successfully managing AEs may help limit their impact on adherence, and following dosage and administration recommendations for iron chelators such as deferasirox may help minimise AEs and optimise treatment in patients with transfusion‐dependent thalassaemia and lower‐risk MDS.